2007
DOI: 10.1207/s15327833mtl0901_2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Demands and Second-Language Learners: A Framework for Analyzing Mathematics Instructional Contexts

Abstract: The issues involved in teaching English language learners mathematics while they are learning English pose many challenges for mathematics teachers and highlight the need to focus on language-processing issues related to teaching mathematical content. Two realistic-type problems from high-stakes tests are used to illustrate the complex interactions between culture, language, and mathematical learning. The analyses focus on aspects of the problems that potentially increase cognitive demands for second-language … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…Hence, it is essential for teachers to provide EBs with scaffolding in this first phase so they can fully understand the problem statement and expectations before they begin the solving process. Research has suggested that EBs are capable of problem solving if they understand the problem statements (Campbell et al, 2007).…”
Section: Prior Research Of Set-up and Emergent Bilingualsmentioning
confidence: 99%
See 4 more Smart Citations
“…Hence, it is essential for teachers to provide EBs with scaffolding in this first phase so they can fully understand the problem statement and expectations before they begin the solving process. Research has suggested that EBs are capable of problem solving if they understand the problem statements (Campbell et al, 2007).…”
Section: Prior Research Of Set-up and Emergent Bilingualsmentioning
confidence: 99%
“…Thus, the differences among learners can be negotiated and understood through conversations and social interactions. Eventually, a common space (Campbell, 2007) will be constructed where they understand each other while their differences still exist.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
See 3 more Smart Citations